Variant-specific deleterious mutations in the SARS-CoV-2 genome reveal immune responses and potentials for prophylactic vaccine development - Islam, Md. Aminul; Shahi, Shatila; Marzan, Abdullah Al; Amin, Mohammad Ruhul; Hasan, Mohammad Nayeem; Hoque, M. Nazmul; Ghosh, Ajit; Barua, Abanti; Khan, Abbas; Dhama, Kuldeep; Chakraborty, Chiranjib; Bhattacharya, Prosun; et al. (Frontiers in Pharmacology, 2023)
Coronavirus disease 2019 (COVID-19), caused by SARS-CoV-2, has had a devastating effect on the world's population during more than last two years due to widespread infections of SARS-CoV-2 and its emerging variants. As of October 12, 2022, more than 600 million confirmed cases and around 6.5 million deaths have been reported due to SARS-CoV-2 infections amidst multiple waves of the COVID-19 pandemic. SARS-CoV-2, like other RNA viruses, is more prone to genetic evolution and dynamic mutations over time, resulting in the continuous emergence of multiple variants that have different characteristics compared to its ancestral strains. Altering genetic mutations of SARS-CoV-2 variants increase its transmissibility, virulence, and disease severity, and decrease the effectiveness of therapeutics and vaccines, causing vaccine breakthrough infections, re-infection, and high mortality and morbidity rates. To assess the rapid spread and emergence of sets of mutations in the SARS-CoV-2 genome, we comprehensively analyzed 10,531 complete genome sequences including all variants reported so far from six continents of the world. NextCladeCLI 2.3.0 (https://clades.nextstrain.org/) and NextStrain (https://nextstrain.org/) open data sources were searched for tracking the SARS-CoV-2 mutations using PROVEAN, Polyphen, and Predict SNP online tools. Genome-wide annotations revealed 16,954 mutations in the SARS-CoV-2 genome compared to Wuhan-Hu-1 reference strain NC_045512.2. We found that the Omicron variant possessed 6,307 mutations (retrieved sequence: 1947) including 67.8% unique mutations. The spike protein of the Omicron variant harbored 876 mutations, including 512 unique and 443 deleterious mutations. Among these mutations, 187 were common and 256 were unique deleterious non-synonymous mutations. Remarkably, Omicron (B.1.1.529 ) variant possessed more deleterious and unique mutations than other variants studied. By analyzing 1,884 sequences of the Delta variant, we detected 4,468 mutations, of which 66% were solely associated with this variant (unique mutations; not reported in other variants). Therefore, these results imply that the Omicron variant is highly transmissible and a variant of concern. This Omicron variant could be prevented if the deleterious and highly frequent unique immunosuppressive mutations can be targeted for vaccine or small-molecule inhibitor designing.